Prospective Assessment of Daily Patterns of Mood-Related Symptoms - Pilz, Luísa K.; Carissimi, Alicia; Francisco, Ana Paula; Oliveira, Melissa A. B.; Slyepchenko, Anastasiya; Epifano, Kristina; Garay, Luciene L. S.; Fabris, Raul C.; Scop, Marina; Streiner, David L.; Hidalgo, Maria Paz; Frey, Benicio N. (Frontiers in Psychiatry, 2018)
Background: The Mood Rhythm Instrument (MRI) is a new self-report questionnaire that aims to assess, the presence and timing of daily patterns of mood-related symptoms. Here, we examined the reliability of the MRI against a prospective daily investigation over the course of 15 days. As a secondary aim, we examined whether the number of items with a perceived daily pattern correlated with severity of depressive symptoms and psychological well-being. Methods: 32 participants recruited from the general population were asked to prospectively fill out a daily version of the MRI (MRI-d) for 15 days. On the 16th day, they filled out the MRI, the Beck Depression Inventory (BDI) and the World Health Organization 5-item well-being index (WHO-5). Results: The MRI showed high agreement with the MRI-d, which suggests that the MRI is a valid tool to assess daily patterns of mood symptoms. The number of mood symptoms perceived as having daily peaks correlated positively with BDI scores and negatively with WHO-5 scores. Conclusion: The MRI might be a valid tool to investigate the presence of daily patterns and the timing of mood-related factors. The MRI does not seem to be influenced by recall or recency biases. Future studies should test the usefulness of this new clinical instrument in individuals with mood disorders, as well as its ability to detect changes in the daily timing of mood symptoms before and after treatment.